Bai Hu Tang, Si Ni Tang, and Xue Bi Tang amplify pro-inflammatory activities and reduce apoptosis in endothelial cells in a cell culture model of sepsis. (28th October 2018) - Brislinger, Dagmar; Daxböck, Christine; Roßmanith, Eva; Stückler, Manuela; Lang, Ingrid; Falkenhagen, Dieter
Abstract: Ethnopharmacological relevance: Sepsis is a systemic inflammatory response of the body to a severe infection or massive tissue injury. Despite intensive research, sepsis continues to have a high mortality rate and successful treatment options are strongly needed. Bai Hu Tang (BHT), Si Ni Tang (SNT), and Xue Bi Tang (XBT) are ancient traditional Chinese formulas derived from Chinese herbs that are used to treat Sepsis, but their mechanisms of activity are largely unknown. Aim of the study: We aimed to examine dose-dependent effects of BHT, SNT, and XBT in a cell culture model of Sepsis, with special focus on endothelial cell apoptosis and the expression of monocyte chemoattractant protein-1 (MCP-1), interleukin (IL)6, IL8, the surface adhesion molecule intercellular adhesion molecule-1 (ICAM-1) and endothelial-leukocyte adhesion molecule-1 (ELAM-1). Material and methods: We stimulated THP1 monocytic cells with lipopolysaccharide (LPS, Escherichia coli (E. coli)) for 4 h and used the resulting culture medium to stimulate human umbilical vein endothelial cells (HUVECs). HUVECs were also simultaneously treated with hydrophilic concentrates of BHT, SNT or XBT. We evaluated the mRNA and protein expression levels of IL6, IL8, MCP-1, ICAM-1, and ELAM-1 and the activity of caspase 3/7, a marker of cell apoptosis, after stimulation and treatment. In addition, we stimulated cannulated veins from human umbilical cords for 24 h and treated them with BHT, SNT or XBT. Immunohistochemistry visualized expression of ICAM-1 and ELAM-1. Results: The mRNA and protein levels of IL6, IL8, ICAM-1, and ELAM-1 were higher in stimulated HUVECs than in controls. Treating stimulated HUVECs with BHT, SNT or XBT induced an additional increase in IL6 (13- to 132-fold) and IL8 (17- to 32-fold) mRNA levels but did not influence their protein levels. In addition, BHT induced an additional increase in ICAM-1 mRNA (9-fold) expression, whereas XBT increased the mRNA and protein levels of ELAM-1 by 42-fold and 10-fold, respectively. Finally, caspase 3/7 levels, and therefore apoptosis, were up to 100% lower in cells treated with BHT than in the stimulated control (P < 0.001). Conclusion: The results of this study indicate that BHT, SNT, and XBT interfere in inflammatory pathways during septic processes by reducing the apoptotic effects of LPS and modifying the endothelial expression of pro-inflammatory cytokines and surface adhesion molecules. Graphical abstract: